Effect of cattle and wildlife exclusion areas on the survival and growth of Pinus culminicola Andresen & Beaman - Jiménez Pérez, Javier; Yerena Yamallel, José Israel Israel; Alanís Rodríguez, Eduardo; Aguirre Calderón, Oscar Alberto; Martínez Barrón, René Alejandro (Ecosistemas y Recursos Agropecuarios, 2018)
In 1997, a restoration of Pinus culminicola was established under three exclusion areas: E1 = cattle plus small mammal exclusion, E2 = cattle exclusion and E3 = no exclusion (free range), in the Cerro El Potosi Protected Natural Area, located in Nuevo León, Mexico. The objective of this study was to determine the survival rate and the increase in diameter and height of Pinus culminicola individuals at three and 17 years after planting. The results show differences between 2000 and 2014 in survival rate and diameter and height growth in the three exclusion areas; E1 and E2 recorded higher averages. The main causes of mortality in this species are attributed to extreme weather conditions and the damage caused by cattle and small mammals.